2019
DOI: 10.1002/biof.1565
|View full text |Cite
|
Sign up to set email alerts
|

Glucorticoid‐induced obesity individuals have distinct signatures of the gut microbiome

Abstract: The human intestine and its resident microbiota are known to play an essential role in the pathogenesis of primary obesity. However, a little is known of the gut microbiota profiles in individuals with obesity induced by glucocorticoid (GC) therapy. Here, we recruited 28 people with GC‐induced obesity and 27 age‐ and gender‐matched healthy controls, whose feces have been collected separately, to delineate the gut microbial characteristics in GC‐induced obesity individuals. High‐throughput Illumina sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
3
29
1
2
Order By: Relevance
“…and ) showed an overall increase in the relative abundance of Clostridiales and a decrease in Bacteroidales and Verruomicrobiales groups. Our changes are consistent with published studies that examined the microbiota following GC‐Tx in mice and more importantly similar changes were observed in GC‐Tx humans . The latter indicates the potential for translation of our findings to humans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and ) showed an overall increase in the relative abundance of Clostridiales and a decrease in Bacteroidales and Verruomicrobiales groups. Our changes are consistent with published studies that examined the microbiota following GC‐Tx in mice and more importantly similar changes were observed in GC‐Tx humans . The latter indicates the potential for translation of our findings to humans.…”
Section: Discussionsupporting
confidence: 92%
“…Our changes are consistent with published studies that examined the microbiota following GC-Tx in mice (31) and more importantly similar changes were observed in GC-Tx humans. (114) The latter indicates the potential for translation of our findings to humans. These studies are particularly interesting because different GC molecules were used (prednisolone, prednisone or dexamethasone), indicating that GC treatment in general may have a reliable effect on fecal bacterial groups and microbial dysbiosis.…”
Section: Discussionmentioning
confidence: 70%
“…Kim JW et al reported that the Firmicutes/Bacteroidetes ratio was consistently reduced in systemic lupus erythematosus (SLE) patients [23]. On the contrary, Qiu D et al reported that the bacterial communities of the glucocorticoidinduced obesity group of people were increased in Firmicutes and decreased in Bacteroidetes compared with the healthy controls [24]. Zhao L et al reported that the ratio of Firmicutes/Bacteroidetes was higher in type 2 diabetes (T2D) patients than the healthy controls [25].…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, two recent studies reported that glucocorticoids induce gut microbial alterations in mice. (Schepper et al, 2019) and humans (Qiu et al, 2019). In human subjects diagnosed for acute transverse myelitis, 3 months treatment with prednisone promoted enrichment in Firmicutes and depletion in Bacteroidetes (Qiu et al, 2019).…”
Section: Drugs Used To Treat Covid-19 and Microbiotamentioning
confidence: 99%